The Procedures and The Language Expressions Used in Handling Guests at Buleleng Regency Tourism Office - Suryanatha , Putu Hady (Jurnal Penelitian Mahasiswa Indonesia, 2023)
In handling guests, certainly several essential references or regulations must be understood by all actors in the tourism sector. Not only in the tourism sector but in government offices knowledge needed to know of reasonable and correct service procedures is required. In carrying out a service to guests visiting the Buleleng Regency Tourism Office, it is necessary to pay attention to the procedures and the correct language expressions. There are some examples of the procedures and the language expressions used when handling the visiting guests that need to be used. With the topic to be discussed, it is hoped that readers can gain knowledge about the procedures and the language expressions used when handling guest visits.